Peningkatan Kemampuan Penalaran Matematika Melalui Metode Project Based Learning Bagi Siswa Kelas VII H Semester GenapMTs Negeri Surakarta II Tahun 2014/2015 - Purnamasari, Dian, Dr. Sumardi, M.Si (2015)
This research aims to identify and describe the improved reasoning ability of students in learning mathematics with project based learning method. This research is a class act or Classroom Action Research (CAR). The receiver of research subject who are acted the student of class VII H MTs Negeri Surakarta II totaling 37 students. The subject of research who are matemathics teacher class VII H. The data collection technique through interview, observation, field notes, testing, and documentation. The validity of data using triangulation of sources and triangulation of technique. Based on these research results of increase reasoning students mathematics can refer to indicators are: (1) the pronouncement serve before action by 29,73% and finally action by 75,68%, (2) the proof arranged or gifted reason about truth solution before action by 24,32% and finally action by 79,38%, (3) the ability to draw conclusions before the action by 13,51% and finally the action by 64,86%. This reseach concluded that the project based learning method in mathematics can improved reasoning ability of students.